Dry Cupping Has Effect On The Reduction Of The Pain Scale In Administrative With Uric Acid - Fakhrudin Nasrul Sani; Totok Wahyudi; Mellia Silvy Irdianty; Diva Agustinaningrum; Putri Alya Rifqi; Riska Putri Sejati (LPPM Universitas Duta Bangsa Surakarta, 2021)
Increased uric acid levels are a degenerative disease experienced by the elderly. Excess uric acid levels in the blood if not immediately prevented and treated will be dangerous because they cause joint pain and the onset of thopia. Dry cupping is a process of cupping with a pump without bleeding. This study aims to determine the effect of dry cupping on reducing pain scale in elderly with gout in Masaran Sragen Village. This research is a quasy experiment with a one group pretest and posttest design. The study population was the elderly with gout pain in the village of Masaran Sragen, amounting to 33 people. Sampling in this research is using total sampling technique. The data analysis used the Wilxocon test because after the normality of the data the results were not normal. The results showed that the average pain scale of respondents before and after being given dry cupping, the pain scale 6 became the pain scale 3.The results of the correlation test analysis showed that there was an effect of giving red ginger foot soaking on the blood pressure of hypertensive patients, indicated by the p-value. = 0.0001 (p-value <0.05).